COMPETENT APPROACH IN EDUCATION: PROBLEMS AND SOLUTIONS - Uljalgas Tulegenkizi Abdullayeva (Galaxy International Interdisciplinary Research Journal, 2023)
The article discusses a number of aspects of education based on competencybased approaches. In particular, the types of professional, practical competencies and their stages of development were discussed.